1991
DOI: 10.7547/87507315-81-10-561
|View full text |Cite
|
Sign up to set email alerts
|

Bullosis diabeticorum. A report of two cases with a review of the literature

Abstract: Bullosis diabeticorum is a rare complication of long-standing diabetes mellitus. Bullous lesions, which appear like burn-induced blisters, occur suddenly without trauma in the feet. These bullae heal spontaneously without scarring; however, recurrence is common. The etiology of bullosis diabeticorum remains unknown. Several theories exist as to causal and contributory factors related to this cutaneous manifestation of diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Larger blisters may be aspirated, using a small bore syringe and aseptic technique, to reduce discomfort and prevent accidental rupture. Some authors have reported flushing the lesion with povidone‐iodine, 16 but we do not believe this is necessary. The blister skin provides a good covering for the lesion and should be left intact, if possible.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Larger blisters may be aspirated, using a small bore syringe and aseptic technique, to reduce discomfort and prevent accidental rupture. Some authors have reported flushing the lesion with povidone‐iodine, 16 but we do not believe this is necessary. The blister skin provides a good covering for the lesion and should be left intact, if possible.…”
Section: Discussionmentioning
confidence: 85%
“… 16 The bullae are intraepidermal (subcorneal to suprabasilar) in some patients and subepidermal in others. 13–24 In most published cases, there is intraepidermal cleavage without acantholysis situated in the superficial part of the prickle‐cell layer 1,25 . This differs from the hemorrhagic type of bullae that heal with atrophy and scarring; these show a cleavage plane below the dermoepidermal junction and destruction of anchoring fibrils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications include metastatic abscesses of the kidneys, lungs, bones, and other organs. 33 A carbuncle appears as a hard and painful red lump that rapidly grows to a diameter of 3 to 10 cm within a few days ( Figure 1G ). After 5 to 7 days, suppuration occurs, with pus discharge from multiple follicular orifices and inflammatory infiltration extending into the subcutaneous and fascial tissues.…”
Section: Furuncles and Carbunclesmentioning
confidence: 99%